Precise Asymptotics in the Law of the Iterated Logarithm under Sublinear Expectations. (12th February 2021) - Xu, Mingzhou; Cheng, Kun
Abstract : By an inequality of partial sum and uniform convergence of the central limit theorem under sublinear expectations, we establish precise asymptotics in the law of the iterated logarithm for independent and identically distributed random variables under sublinear expectations.